Research advances of triglyceride-glucose index for chronic kidney disease and coronary artery disease - Guan Xiao-yang; Liu Hong (Linchuang shenzangbing zazhi)
Chronic kidney disease（CKD）has become a global public health problem with its constantly rising morbidity.As a common complication, cardiovascular disease（CVD）is a leading cause of death in CKD patients.And coronary artery disease（CAD）predominates.Insulin resistance（IR）is a potential causative mechanism of CKD/CAD.Triglyceride-glucose index（TyG index）is an effective tool for IR evaluation.This review summarized the relationship of TyG index with CKD/CAD.